Vaavubhali, a Traditional Festival for Remembering Ancestors - Franco, F; Robin, D. (University of Hawaii Press, 2011)
Remembering ancestors is a part of tradition in every society. In this article, we present the importance of a traditional festival called vaavubhali in the context of ecological and economical services rendered. The festival honours deceased souls and also popularizes the planting of ornamental, medicinal and timber yielding plants. The changing scenario is also depicted.